2007
DOI: 10.1093/hmg/ddm292
|View full text |Cite
|
Sign up to set email alerts
|

The grainyhead like 2 gene (GRHL2), alias TFCP2L3, is associated with age-related hearing impairment

Abstract: Age-related hearing impairment (ARHI) is the most prevalent sensory impairment in the elderly. ARHI is a complex disease caused by an interaction between environmental and genetic factors. The contribution of various environmental factors has been relatively extensively studied. In contrast, investigations to identify the genetic risk factors have only recently been initiated. In this paper we describe the results of an association study performed on 2418 ARHI samples derived from nine centers from seven Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 48 publications
4
107
1
2
Order By: Relevance
“…Intriguingly, the SNP rs161927 (P-value 0.000149), that ranked eighth for PC1, was positioned immediately downstream from the metabotropic GRM7 gene. A previous GWAS of a European and a Finnish sample set, which was based on an age-and gendercorrected Z-score highly correlated with our PC1, 9,11,28,42 already suggested a role for GRM7 in ARHI. 9 GRM7 encodes a metabotropic glutamate receptor that can be activated by L-glutamate, the primary excitatory neurotransmitter in the cochlear hair cell.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Intriguingly, the SNP rs161927 (P-value 0.000149), that ranked eighth for PC1, was positioned immediately downstream from the metabotropic GRM7 gene. A previous GWAS of a European and a Finnish sample set, which was based on an age-and gendercorrected Z-score highly correlated with our PC1, 9,11,28,42 already suggested a role for GRM7 in ARHI. 9 GRM7 encodes a metabotropic glutamate receptor that can be activated by L-glutamate, the primary excitatory neurotransmitter in the cochlear hair cell.…”
Section: Discussionsupporting
confidence: 58%
“…8 In addition, several association studies based on a candidate gene approach and two genome-wide association studies (GWAS) 8,9 have been conducted. Early candidate gene-based association studies are reviewed by Van Eyken et al 10 Recently, based on a candidate gene approach, we reported associations between ARHI and variants in GRHL2, 11 encoding a transcription factor that is also involved in monogenic hearing loss. In addition, based on a pooling GWAS, we reported association with variants in the glutamate receptor-7 gene (GRM7), 9 encoding a metabotropic glutamate receptor assumed to modulate hair cell excitability and synaptic efficacy.…”
Section: Introductionmentioning
confidence: 91%
“…9 Phenotypes were described using Principal component (PC) scores, as described in Supplementary data. In total, PC scores were obtained for 2161 individuals.…”
Section: Sample Collection and Phenotypingmentioning
confidence: 99%
“…4,5 This protein expressed in epithelial structures acts as a transcriptional activator, regulating epidermal development. 6,7 GRHL2 is associated with age-related hearing impairment, 8 neural tube closure, 9 epidermal integrity, 10 wound healing, 11 and the regulation of many physiological functions of human airway epithelium. 12 In the context of cancer, GRHL2 has been reported to function as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%